2010
DOI: 10.1016/j.mambio.2008.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of the southern Patagonian-Fueguian endemic Abrothrix lanosus (Rodentia: Sigmodontinae): Phylogenetic position, karyotypic and morphological data

Abstract: Abrothrix lanosus (Thomas, 1897) is morphologically redescribed on the basis of new specimens collected in Tierra del Fuego (Argentina). Cranial, mandibular, skeletal, penile, and chromosomal characteristics are described and compared with other species of Abrothrix, especially those of the Patagonian-Fueguian region. Its phylogenetic position within Abrotrichini is explored using DNA sequences of the mitochondrial cytochrome b (cyt b) and the nuclear Interphotoreceptor Retinoid Binding Protein (IRBP) genes. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 38 publications
0
33
1
4
Order By: Relevance
“…Given that previous studies showed discrepancies between the topologies of different sigmodontine gene trees (e.g., Feijoo et al 2010;Teta et al 2011), the fact that different datasets (i.e., IRBP or Cyt b matrices with slightly different taxonomic sampling) provide different relationships for Abrawayaomys is not unexpected. Importantly, with the exception of the BA based on Cyt b sequences (sister to Reithrodontini), no sister relationship involving Abrawayaomys was recovered that had good support.…”
Section: Discussionmentioning
confidence: 84%
“…Given that previous studies showed discrepancies between the topologies of different sigmodontine gene trees (e.g., Feijoo et al 2010;Teta et al 2011), the fact that different datasets (i.e., IRBP or Cyt b matrices with slightly different taxonomic sampling) provide different relationships for Abrawayaomys is not unexpected. Importantly, with the exception of the BA based on Cyt b sequences (sister to Reithrodontini), no sister relationship involving Abrawayaomys was recovered that had good support.…”
Section: Discussionmentioning
confidence: 84%
“…Phylogenetic relationships of the tribe Abrotrichini have been evaluated chiefly with molecular markers (e.g. D′Elía, ; D'Elía et al., ; Rodríguez‐Serrano et al., ; Feijoo et al., ; Teta et al., ; Cañón et al., ). These studies confirmed tribal monophyly as well as a major division between cursorial forms of the genus Abrothrix and the fossorial long‐clawed Abrotrichini, consisting of the genera Chelemys , Geoxus , Notiomys and Pearsonomys .…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, molecular evidence has clarified the interrelationships among the members of this tribe (e.g. D'Elía et al., , ; Rodríguez‐Serrano et al., ; Feijoo et al., ). One of the main conclusions was that Abrotrichini comprises two principal clades, one encompassing the mostly long‐clawed forms Chelemys , Geoxus , Notiomys and Pearsonomys , and the other restricted to the cursorial/scansorial taxa of the genus Abrothrix .…”
Section: Main Taxonomic Hypotheses For the Genera Now Referred To Abrmentioning
confidence: 99%
“…We used the tree from Parada et al (2013) as a reference to construct our phylogenetic matrix. This tree was reduced to the main groups used in this study and we added the species not included based on several morphological and molecular studies (D'Elía 2003; Rivera et al 2007;Steppan Fig Rivera et al 2007;Steppan et al 2007;Feijoo et al 2008;Mares et al 2008;Jayat et al 2010;Parada et al 2013;Salazar-Bravo et al 2013;Teta et al 2013Teta et al ) et al 2007Feijoo et al 2008;Mares et al 2008;Jayat et al 2010;Salazar-Bravo et al 2013;Teta et al 2013) (Fig. 3).…”
Section: Holochilus Chacarius Weskler (2006) Natatorialmentioning
confidence: 99%